PERBEDAAN ANTARA KLAUSA SUBORDINATIF BAHASA INDONESIA DAN BAHASA INGGRIS - Anisak Syaid Fauziah; Mustofa Kamal; Djatmika Djatmika; Sumarlam Sumarlam (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
The aim of this study was to describe the difference between subordinate in Indonesian and in English viewed from subordinate clause theory from Jim Miller. This study used qualitative descriptive approach.  Primary data of this study were written texts containing sentences and clauses in English and Indonesian the corpus of which was selected from academic texts.  Data were collected using record.  Segmenting immediate constituent was used to analyze the data.  The research revealed that Indonesian has neither elliptic conjunction in all relative and adverbial clauses nor non-finite subordinate clauses. English has no elliptic conjunction only in relative clauses showing possessiveness and all adverbial clauses except for time and result but has non-finite subordinate clauses. Indonesian has no relative clause elliptic conjunction non-finite subordinate clause. English relative clause elliptic conjunction is available and  empty elliptic conjunction in all adverbial clauses appear. English has non-finite subordinate clauses.